PSSI Management in Developing Football Achievement in Kerinci Regency - Gito Ameza Leflindo; Fahd Mukhtarsyaf; Ridho Bahtra; Iit Selviani; Nugroho Susanto (Darul Yasin Al Sys, 2026)
The sustainable development of regional football achievement requires systematic management capable of optimizing athletes’ potential. In Kerinci Regency, however, limited funding, inadequate training facilities, a shortage of licensed coaches, and weak athlete data management continue to constrain the effectiveness of football development. This study aims to analyze the management of the Indonesian Football Association (Persatuan Sepak Bola Seluruh Indonesia [PSSI]) in developing football achievement in Kerinci Regency based on the management functions of planning, organizing, directing, and controlling. A descriptive qualitative approach was employed, involving in-depth interviews with ten informants selected through purposive and snowball sampling. Data were analyzed using the Miles and Huberman interactive model, comprising data reduction, data display, and conclusion drawing. The findings indicate that PSSI Kerinci Regency has implemented the core management functions in developing football achievement, although their application remains suboptimal. Athlete development programs have been systematically designed and implemented in stages, the organizational structure and division of responsibilities have been established, and program evaluations are conducted periodically. Nevertheless, implementation is constrained by limited financial resources, insufficient human-resource capacity, inadequate training facilities, a shortage of licensed coaches, and an unstructured athlete documentation system. The study concludes that strengthening strategic planning, improving human-resource quality and training infrastructure, and enhancing collaboration among PSSI, the Indonesian National Sports Committee (Komite Olahraga Nasional Indonesia [KONI]), and the local government are essential for supporting the sustainable development of football achievement in Kerinci Regency. These findings contribute practical insights into strengthening regional sports-management systems and improving institutional coordination in football development.